Dental Implantology and Biomaterial 2016
DOI: 10.5772/64066
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Materials as an Alternative to Titanium for Dental Implant Fabrication

Abstract: Titanium is the gold standard material to produce dental implants from more than years, showing high success rate in different clinical scenarios. Zirconia implants were recently introduced to overwhelm some aesthetic and biological problems that can arise from titanium. Preclinical studies show that, from a mechanical point of view, zirconia may be a suitable substitute for titanium in implant fabrication. Three-dimensional finite element analysis FE" models found no difference between titanium and titaniumzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the pursuit of enhancing dental implant materials, zirconia has drawn significant attention due to its superior biocompatibility, esthetically pleasing nature, high corrosion resistance, good mechanical properties, and absence of reported allergic reactions [ 6 ]. Furthermore, zirconia implants have been introduced to overcome esthetic and biological problems that can arise from titanium [ 7 ]. However, it is essential to note that zirconia implants may exhibit a slower initial osseointegration process compared to titanium implants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of enhancing dental implant materials, zirconia has drawn significant attention due to its superior biocompatibility, esthetically pleasing nature, high corrosion resistance, good mechanical properties, and absence of reported allergic reactions [ 6 ]. Furthermore, zirconia implants have been introduced to overcome esthetic and biological problems that can arise from titanium [ 7 ]. However, it is essential to note that zirconia implants may exhibit a slower initial osseointegration process compared to titanium implants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While ceramics are biocompatible and esthetic, their durability and fracture resistance must meet the criteria to replace conventional metal–ceramic crowns [ 8 , 9 ]. Findings from a laboratory study comparing the fracture resistance of zirconia and lithium disilicate monolithic crowns, which were cemented onto zirconia hybrid abutments, indicated that these materials exhibit resistance to molar masticatory forces and yield satisfactory results [ 10 ].…”
Section: Introductionmentioning
confidence: 99%